Does Endoscopic Ultrasound Improve Detection of Locally Recurrent Anal Squamous-Cell Cancer?. Issue 2 (February 2015) - Peterson, Carrie Y.; Weiser, Martin R.; Paty, Philip B.; Guillem, Jose G.; Nash, Garrett M.; Garcia-Aguilar, Julio; Patil, Sujata; Temple, Larissa K.
<x xml:space="preserve">Abstract</x> BACKGROUND: Evaluating patients for recurrent anal cancer after primary treatment can be difficult owing to distorted anatomy and scarring. Many institutions incorporate endoscopic ultrasound to improve detection, but the effectiveness is unknown. OBJECTIVE: The aim of this study is to compare the effectiveness of digital rectal examination and endoscopic ultrasound in detecting locally recurrent disease during routine follow-up of patients with anal cancer. DESIGN: This study is a retrospective, single-institution review. SETTINGS: This study was conducted at an oncologic tertiary referral center. PATIENTS: Included were 175 patients with nonmetastatic anal squamous-cell cancer, without persistent disease after primary chemoradiotherapy, who had at least 1 posttreatment ultrasound and examination by a colorectal surgeon. MAIN OUTCOME MEASURES: The primary outcomes measured were the first modality to detect local recurrence, concordance, crude cancer detection rate, sensitivity, specificity, and predictive value. RESULTS: Eight hundred fifty-five endoscopic ultrasounds and 873 digital rectal examinations were performed during 35 months median follow-up. Overall, ultrasound detected 7 (0.8%) mesorectal and 32 (3.7%) anal canal abnormalities; digital examination detected 69 (7.9%) anal canal abnormalities. Locally recurrent disease was found on biopsy in 8 patients, all detected first or only with digital examination. Four patients did not have an ultrasound at the time of diagnosis of recurrence. The concordance of ultrasound and digital examination in detecting recurrent disease was fair at 0.37 (SE, 0.08; 95% CI, 0.21–0.54), and there was no difference in crude cancer detection rate, sensitivity, specificity, and negative or positive predictive values. LIMITATIONS: The heterogeneity of follow-up timing and examinations is not standardized in this study but is reflective of general practice. CONCLUSIONS: Endoscopic ultrasound did not provide any advantage over digital rectal examination in identifying locally recurrent anal cancer, and should not be recommended for routine surveillance.